Между Прустом и Джойсом: Вехи на пути к Aбсолюту [Between Proust and Joyce: Markers on the way to the Absolute] - Demidova, Olga (Slavica Revalensia, 2015)
In this article Olga Demidova provides a detailed analysis of the critical reception of Marcel Proust and James Joyce in Russian émigré literature of the Interwar years. She suggests that responses of émigrés to Proust and Joyce were essentially self-descriptive: when writers compared a peer to Proust or Joyce, they were primarily expressing their own aesthetic and ethical framework.